2013
DOI: 10.1371/journal.pone.0066613
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Glucocorticoids Inhibited Early Immune Responses and Impaired Cardiac Repair in Adult Zebrafish

Abstract: Myocardial injury, such as myocardial infarction (MI), can lead to drastic heart damage. Zebrafish have the extraordinary ability to regenerate their heart after a severe injury. Upon ventricle resection, fibrin clots seal the wound and serve as a matrix for recruiting myeloid-derived phagocytes. Accumulated neutrophils and macrophages not only reduce the risk of infection but also secrete cytokines and growth factors to promote tissue repair. However, the underlying cellular and molecular mechanisms for how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 40 publications
1
80
0
2
Order By: Relevance
“…Huang et al found that expression of pro-inflammatory cytokine genes, such as il-1ß , tnf-α , il-8 , and inflammatory markers are upregulated after ventricular resection (Huang et al, 2013b). Treating fish after ventricle resection with anti-inflammatory glucocorticoid or nonsteroidal anti-inflammatory drugs resulted in repression of pro-inflammatory cytokine gene transcript levels and a failure to completely regenerate the heart, which correlated with reduced number of lyz :EGFP positive cells in the injured myocardium.…”
Section: Cell Migration During Zebrafish Heart Regenerationmentioning
confidence: 99%
“…Huang et al found that expression of pro-inflammatory cytokine genes, such as il-1ß , tnf-α , il-8 , and inflammatory markers are upregulated after ventricular resection (Huang et al, 2013b). Treating fish after ventricle resection with anti-inflammatory glucocorticoid or nonsteroidal anti-inflammatory drugs resulted in repression of pro-inflammatory cytokine gene transcript levels and a failure to completely regenerate the heart, which correlated with reduced number of lyz :EGFP positive cells in the injured myocardium.…”
Section: Cell Migration During Zebrafish Heart Regenerationmentioning
confidence: 99%
“…In zebrafish, both fin and cardiac regeneration are impaired when activation of the glucocorticoid receptor (GR) is pharmacologically inhibited [21,22]. As activated GRs transactivate genes encoding pro-inflammatory transcription factors such as AP1, STATs, NF-AT and NF-B [23,24], the negative effect observed upon GR inhibition initially suggested that inflammation was playing an active role during regeneration.…”
Section: Immune Processes That Are Neutral To Regenerationmentioning
confidence: 99%
“…ATP release participates in the "find me signal," which attracts phagocytes to the lesion site to resolve the wound [28,23]. The infiltration of macrophages is required for blastema formation in newts regenerating their limbs [29], as well as in adult zebrafish regenerating their caudal fin and their heart [30,31]. Within the first 24 hpa, these macrophages release proteases, growth factors, and cytokines that are important for tissue remodelling and the stimulation of proliferation.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%